(3WQb GdGbJUGO GdbjGSj (B:s (3eMGVQGJ hJWHjbGJ (B/s - (3TjNj, eMeOs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2020)
(3jVe JMdjd GdGfMOGQ GdNWj GdHSjW, JMdjd GdGfMOGQ GdNWj GdYGe, eTGcd GdbjGS GdGbJUGOj GNJQGb aQVjGJ GdfehPL, WQb hJbfjGJ CNQiaj JMdjd GdGfMOGQ, eONd Edi feGPL GdeYGOdGJ GdBfjI, COhGJ JMdjd GdSdGSd GdRefjI, eONd Edi feGPL (BVAR (3eTcd GdJcGed GdeTJQc, feGPL (BARCH (3hJWHjbGJgG GdeGdjI, WQb ZjQ NWjI aj JMdjd GdSdGSd GdRefjI(B.s
(3HjHdjhZQGajG(B: (3U U(B.417-435s
Keywords: (3GdEbJUGO GdJMdjdjs; (3GdGbJUGO GdQjGVjs